Experiment of quality properties of dehydrated fruits - Antal, Tamás (Acta Agraria Debreceniensis, 2008)
The lyophilization is the joint application of freezing and drying. It is an up-to-date conserving procedure, the point of which is that the humidity existing in the frozen humid material is transferred from the solid state directly into the gaseous state at a temperature below 0 oC under vacuum. Out of the procedures applied nowadays, this is the most tolerant drying process.With regard to the high investment and operational costs, freeze drying is applied only for valuable, heat-sensitive materials when the technological aim is to preserve such properties as aroma, taste and colour as well as such components as proteins and vitamins. This procedure is suitable for drying and conserving certain foodstuffs, stimulants, organic chemicals, medicines and similar sensitive and valuable materials.In our institute, we have been conducting freeze drying experiments with regional fruits and vegetables since the year 2005. During the first phase, we examined the heat- and material transfer as well as the abstraction of humidity, while during the second phase we analysed the rehydration ability and nutrient content of the freeze-dried materials as compared to those dried with the method of convection. Moreover we have conducted penetration measurements with a portable hardness tester.To sum up the results gained so far, we can state that the quality of the lyophilized materials is better than those dried in the traditional way. It originates partly in the fact that the temperature and pressure applied for the freeze drying are smaller and the drying period is far longer than for the convection drying.In contrast to convection-dried materials, freeze dried materials set in close to their original water-content, keep their original shape and size after being rehydrated. The reason of it the porous, spongy structure (flexible cell wall) of the lyophilized products which is able to take up moisture quickly. In addition, the lyophilized products can be rehydrated faster than those dried in the traditional way.Regarding the results of the chemical analyses, the following conclusion can be drawn: the vacuum freeze drying results a small decrease of nutrient content and nutritive value for the lyophilized products.The results of the hardness tests support the statement that the majority of agricultural materials cannot be considered as an ideal flexible body, because during the experiment the flexibility coefficient changed when going from the surface of the material inwards. In addition, the penetration tests also confirm that the surface of the convection-dried vegetables is at least 1.5-3 times harder than that of the freeze-dried products. The reason of it that it takes place during the drying denaturation processes.The article summarizes the results of our research work listed above, in accordance with our experiments conducted by using the characteristic fruits (apple, plum) of the Nyírség Region.